Knowledge of HIV testing and attitudes towards blood donation at three blood centres in Brazil. Issue 4 (9th December 2013) - Miranda, C.; Moreno, E.; Bruhn, R.; Larsen, N. M.; Wright, D. J.; Oliveira, C. D. L.; Carneiro‐Proietti, A. B. F.; Loureiro, P.; de Almeida‐Neto, C.; Custer, B.; Sabino, E. C.; Gonçalez, T. T.; et al.
<x xml:space="preserve">Abstract</x> Background Reducing risk of HIV window period transmission requires understanding of donor knowledge and attitudes related to HIV and risk factors. Study Design and Methods We conducted a survey of 7635 presenting blood donors at three Brazilian blood centres from 15 October through 20 November 2009. Participants completed a questionnaire on HIV knowledge and attitudes about blood donation. Six questions about blood testing and HIV were evaluated using maximum likelihood chi‐square and logistic regression. Test seeking was classified in non‐overlapping categories according to answers to one direct and two indirect questions. Results Overall, respondents were male (64%) repeat donors (67%) between 18 and 49 years old (91%). Nearly 60% believed blood centres use better HIV tests than other places; however, 42% were unaware of the HIV window period. Approximately 50% believed it was appropriate to donate to be tested for HIV, but 67% said it was not acceptable to donate with risk factors even if blood is tested. Logistic regression found that less education, Hemope‐Recife blood centre, replacement, potential and self‐disclosed test‐seeking were associated with less HIV knowledge. Conclusion HIV knowledge related to blood safety remains low among Brazilian blood donors. A subset finds it appropriate to be tested at blood centres and may be unaware of the HIV window period. These donations may impose a significant risk to the safety of the blood supply. Decreasing test‐seeking and changing beliefs about the appropriateness of individuals with behavioural risk factors donating blood could reduce the risk of transfusing an infectious unit.